(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk S, Saensouk P. 2021. Karyotype analysis of three species of Allium (Amaryllidaceae) from Thailand. Biodiversitas 22: 3458-3466. Comprehensive karyotype analysis of three species of Allium from Thailand has not been reported. This work aims to study karyotype analysis of three species of Allium from Thailand. It is confusing due to the use of the common name or local name or local Thai name and morphologies. The karyotype analysis of three species with two variations in the genus Allium from Thailand were studied from root tips and observed under a microscope then karyotype was obtained from 10 metaphase plates. The chromosome numbers of them were found 2n = 16. The karyotype formulas of them were constructed as 14m + 2st (Allium ascalonicum L. or shallot), 12m + 2sm + 2st (A. cepa L. or onion), 10m + 6sm (1 sat) (A. cepa L. or red onion), 10m + 4sm + 2st (A. sativum L. or big garlic or Chinese garlic) and 8m + 6sm + 2st (A. sativum L. or small garlic or Thai garlic). Chromosome structure differences among the three species appeared in the number of m, sm and st chromosomes and the satellites at the end of the short arm of A. cepa L. (red onion). This is new data on chromosome structure of the genus Allium. Moreover, the karyotype formulas, chromosome structures and satellites of this study should be used for classification of Allium from Thailand.